2020
DOI: 10.1016/j.bja.2019.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ventilation strategies to prevent postoperative pulmonary complications: a network meta-analysis of randomised controlled trials

Abstract: Background: The debate on lung-protective ventilation strategies for surgical patients is ongoing. Evidence suggests that the use of low tidal volume V T improves clinical outcomes. However, the optimal levels of PEEP and recruitment manoeuvre (RM) strategies incorporated into low V T ventilation remain unclear. Methods: Several electronic databases were searched to identify RCTs that focused on comparison between low V T strategy and conventional mechanical ventilation (CMV), or between two different low V T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 54 publications
1
45
0
1
Order By: Relevance
“…Two previous meta-analysis studies found a significant difference between protective ventilation and conventional ventilation in acute respiratory distress syndrome ( 52 , 53 ). However, similar to our results another meta-analysis study did not find any significance in acute respiratory distress syndrome ( 54 ). The difference may be because of different methodologies used in those studies.…”
Section: Discussionsupporting
confidence: 90%
“…Two previous meta-analysis studies found a significant difference between protective ventilation and conventional ventilation in acute respiratory distress syndrome ( 52 , 53 ). However, similar to our results another meta-analysis study did not find any significance in acute respiratory distress syndrome ( 54 ). The difference may be because of different methodologies used in those studies.…”
Section: Discussionsupporting
confidence: 90%
“…Lung-protective ventilation strategies are known to influence the rate of postoperative complications. 27 However, all participating trial centres used lung-protective ventilation strategies with low-to-modest tidal volumes, positive end-expiratory airway pressure of at least 5 cm H 2 O, and pressure-controlled ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment maneuvers are one of the constituents of optimal intraoperative ventilation ( 17 ) . Their effectiveness has been extensively discussed in literature; however, even based on large meta-analyses the most optimal procedure for performing them has not been determined thus far ( 18 , 19 ) . Because of the risk of both respiratory and circulatory complications (mainly hypotension), it is justified to closely monitor their course, also with the application of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%